Integrating Group Discussion Strategies in MI Evaluation Courses To Enhance Metacognition and Critical Thinking Skills of PGMI Students - Siti Fatimah; Ari Susetiyo (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This study aims to gain an in-depth understanding of the experiences and internal processes of students in the Islamic Elementary Teacher Education (PGMI) Study Program in developing metacognition and critical thinking through the implementation of group discussion strategies in the Evaluation of Learning course. Using a descriptive phenomenological approach, this study involved 18 PGMI students who actively participated in group discussion sessions. Primary data were collected through in-depth interviews, participatory classroom observations, and document analysis. The data were analyzed thematically to identify core categories and emerging themes. The findings revealed two central themes: first, the externalization of cognitive processes, where group discussions served as a medium for metacognitive awareness, encouraging students to recognize, monitor, and evaluate their own thinking strategies; and second, the enhancement of critical thinking, where differences of opinion within the group triggered constructive socio-cognitive conflicts that prompted students to engage in reflective reasoning and argument evaluation. The study highlights that the quality of social interaction within group discussions plays a crucial role in facilitating the internalization of higher-order cognitive skills among prospective Islamic elementary teachers. Overall, group discussion is shown to be not merely an active learning method but a pedagogical strategy that effectively fosters metacognition and critical thinking, shaping reflective and professional teacher candidates in the PGMI program.